Evaluación de la sostenibilidad en la gestión turística de las empresas de alojamiento de tercera y cuarta categoría en Santo Domingo de los Tsáchilas - Guadalupe Hurtado, Lisseth Ivon (2021)
This research was carried out with the objective of evaluating the sustainability in the tourist management of the third and fourth category accommodation companies of the Santo Domingo canton. The type of research was exploratory and descriptive, with a mixed approach. The development of the research was structured in 3 phases. In the first, a situational diagnosis of the canton and the third and fourth category accommodation establishments was carried out, through interviews and surveys of personnel, where it was evidenced that 58% of the establishments do not incorporate sustainable processes in their management, deriving some negative aspects such as: inadequate tourism management, the absence of sustainable policies, the incorrect use of its resources, and the inefficient treatment of solid waste, since only 45% reaches the community causing pollution and damage to the resources surrounding the Business. In the second phase, through a bibliographic analysis, the selection and identification of the indicators was carried out to later apply the Delphi method through the expert validation instrument, resulting in 37 indicators, where: 9 criteria and 19 indicators were of the sociocultural, 4 criteria and 9 indicators of an economic nature, and 6 criteria and 9 indicators of an environmental nature. Finally, in the last phase, the evaluation of accommodation companies was carried out, where 59% do not have sustainable tourism management, so that the need arises to formulate improvement strategies that help mitigate the main problems.